LORIS: a web-based data management system for multi-center studies - Das, Samir; Zijdenbos, Alex P.; Vins, Dario; Harlap, Jonathan; Evans, Alan C. (Frontiers in Neuroinformatics, 2012)
LORIS (Longitudinal Online Research and Imaging System) is a modular and extensible web-based data management system that integrates all aspects of a multi-center study: from heterogeneous data acquisition (imaging, clinical, behavior, genetics) to storage, processing and ultimately dissemination. It provides a secure, user-friendly, and streamlined platform to automate the flow of clinical trials and complex multi-center studies. A subject-centric internal organization allows researchers to capture and subsequently extract all information, longitudinal or cross-sectional, from any subset of the study cohort. Extensive error-checking and quality control procedures, security, data management, data querying and administrative functions provide LORIS with a triple capability (i) continuous project coordination and monitoring of data acquisition (ii) data storage/cleaning/querying, (iii) interface with arbitrary external data processing “pipelines”. LORIS is a complete solution that has been thoroughly tested through the full life cycle of a multi-center longitudinal project# and is now supporting numerous neurodevelopment and neurodegeneration research projects internationally.